The growing presence of women in development - Miriam Krawczyk (CEPAL Review, 1990)
One of the most far-reaching social changes in the Latin American and Caribbean region in the last 30 years has been the ever-increasing presence of women in public life, particularly in education and the work force. This presence has also been significant in social movements and grass-roots organizations.